2023
DOI: 10.4028/p-hbgzq6
|View full text |Cite
|
Sign up to set email alerts
|

Coating Glass Fibre Yarn with Conductive Materials for Real-Time Structure Sensing

Khalid Alblalaihid,
Saleh A. Alghamdi,
Anas Alburayt
et al.

Abstract: Nowadays, the demand for glass fibre-reinforced polymers (GFRPs) has increased in the industry owing to their low weight, high strength, corrosion resistance and low cost compared with other fibre-reinforced polymer composites. However, GFRP is anisotropic material with low interlaminar strength where the damage can occur without warning. Integrating a real-time damage detection process can mitigate this problem. Therefore, this paper presents the initial fabrication of an embedded capacitive sensor into the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Two different materials of filament yarn, namely glass and Kevlar fiber, were considered in this investigation. Various conductive coating techniques were evaluated, and physical vapor deposition (PVD) was selected as the appropriate coating technique, based on previous work [31]. PVD was chosen for its lower operational temperatures, which are vital for avoiding thermal degradation of the fibers and ensuring their continued structural and functional integrity [32].…”
Section: Preparation Of Coated Fibres Yarn (Electrodes) For Capacitiv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two different materials of filament yarn, namely glass and Kevlar fiber, were considered in this investigation. Various conductive coating techniques were evaluated, and physical vapor deposition (PVD) was selected as the appropriate coating technique, based on previous work [31]. PVD was chosen for its lower operational temperatures, which are vital for avoiding thermal degradation of the fibers and ensuring their continued structural and functional integrity [32].…”
Section: Preparation Of Coated Fibres Yarn (Electrodes) For Capacitiv...mentioning
confidence: 99%
“…Additionally, Figure 2i displays images of cured laminates with lateral sensor configurations for glass fiber-reinforced polymer composites. To verify that the problems encountered in prior studies [31], specifically the dispersion of spray carbon coating within the epoxy resin, were not repeated, a gold-coated glass fiber yarn filament embedded in an epoxy resin matrix underwent visual inspection via microscopy post-curing, as depicted in Figure 3e. This examination, carried out using an OLYMPUS MX61L microscope, (Tokyo, Japan), confirmed that the gold coating remained intact without dispersal.…”
Section: Preparation Of Coated Fibres Yarn (Electrodes) For Capacitiv...mentioning
confidence: 99%